Riders waiting for the train at Union Train Station, 1969. - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 10-24-69 p.12. Oversize.
Riders waiting for the train at Union Train Station, 1969.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth